Nutritional Behaviours Of Adolescents Living In Rural Areas. Part 2. Characteristic Of Pro-Health Behaviour In Aspect Of Frequency Of Consuming Meals And Selected Foodstuff - Elżbieta Cipora; Ewa Smoleń; Halina Piecewicz; Jarosław Sobieszczański; Walery Zukow; Anna Sobieszczańska (Kazimierz Wielki University, 2016)
Introduction. Proper nutrition exerts an effect on the quality of life of an individual in each domain of functioning. Many studies indicate that among a high percentage of the population the level of health knowledge is unsatisfactory, which often results from a low quality of life. High deficiency of health knowledge, especially concerning the principles of proper nutrition, is observed especially among children and adolescents. The place of residence is one of the major characteristics which differentiate the level of their knowledge.   Objective. The objective of the study was recognition and evaluation of nutritional behaviours of adolescents attending junior high schools living in rural areas, from the aspect of the frequency of consumption of meals and some food products. Materials and method. The study was conducted in 2015, in a randomly selected rural junior high school in the Sanok province. The study group covered 115 school adolescents. The method of a diagnostic survey was applied, and the research instrument was an author-constructed Questionnaire. Statistical analyses were performed using chi-square test and Cramer's V test. The p values p<0.05 were considered statistically significant. Results.  The respondents were asked about the frequency of consumption of selected food products, considered as those most often consumed, specified according to the evaluation category - pro-health or anti-health. The main analyses were based on data concerning the daily consumption of the selected food products, which allowed an assessment of the types of health behaviours of junior high school adolescents. It was found that the percentage of adolescents who every day consumed fruit, white bread, dairy products and vegetables was higher than the percentage of those who consumed wholemeal bread, sweets, poultry and poultry products.  The adolescents showed health promoting behaviours with respect to the frequency of consumption of fast food, because only 5.2% of them consumed these products every day. Very few respondents admitted that they consumed fish, pork and beef daily. Boys more frequently consumed beef and poultry, while no significant differences according to gender were observed regarding the consumption of sweets, limitation of the number of meals due to stressful situation, and the consumption of the last meal before sleep. Conclusions.  1. Only approximately a half of junior high school adolescents living in rural areas observed the principles of rational nutrition, and in only some of its aspects. 2. The most frequent nutritional errors included too frequent consumption of white bread and sweets, and too rare consumption of, among others, vegetables, fish, wholegrain bread and beef. 3. Insufficient knowledge and frequent anti-health behaviours allow the presumption that it is necessary to carry out long-term health education, using modern activation techniques which are available in the adolescents' life environment, and in the school environment.